CO Oxidation over Metal Oxide Catalyst Supported by Indonesian Natural Zeolite - Purwono, Suryo (ASEAN Journal of Chemical Engineering, 2002)
The objectives of this study are to attempt to develop catalysts and to find the operating conditions under which combustible waste gases concentrations in the exhaust gases can be eventually reduced to satisfy air pollution standards. The results shows that using impregnation method, nickel and vanadium metals, as active components of the catalyst, can be dispersed on the natural zeolite as catalyst support. The reaction rate measurements of catalytic oxidation of CO was done in the temperature range between 300 and 550°C using a differential micro-reactor. The catalysts used for this experiment were vanadium pentoxide and nickel oxide on activated natural zeolite. To avoid fluidization, the reactant gases were flowed downward. The results show that the reaction rate depends strongly on the bed temperature and feed concentration and is not controlled by bulk phase mass transfer and pore diffusion.